PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH PERIODE 2014-2018 - Putri Alma Gholy; Prameswara Samofa Nadya (NISBAH: Jurnal Perbanka Syariah, 2020)
The application of Good Corporate Governance (GCG) is the way to control a corporate professionally and transparently to reach goals agreed by both shareholders and stakeholders. So, it is expected Islamic banks can perform with a good quality and consistently implementing GCG mechanism along with increasing profits. Therefore, this research focused on appraising profitability increasing with Return on Asset (ROA) and Return on Equity (ROE) as indicator, together with appraising GCG with self assessment reports based on 11 criteria of composite rate valuation. This research used quantitative method from GCG reports and annual report of Islamic Banks from 2014-2018 period, as secondary data. The result was GCG as independent variable positively and significantly effecting ROA and ROE.